Can administrative data be used to research health visiting in England? A completeness assessment of the Community Services Dataset - Clery, Amanda; Bunting, Catherine; Liu, Mengyun; Harron, Katie; Woodman, Jenny; Mc Grath-Lone, Louise (International Journal of Population Data Science, 2024)
Introduction Health visiting is a community service provided to families with children under five in England and is a key focus of early years policy. Individual-level data on health visiting is captured in the Community Services Data Set (CSDS), an administrative dataset of publicly funded community services across England. Analyses of CSDS are considered experimental as the dataset matures. Objectives In this study, we aimed to identify health visiting contacts in the CSDS and assess the completeness of these data from 2016/17 to 2019/20 compared to external reference data. Methods We identified the number of the four mandated postnatal health visiting contacts delivered, excluding those scheduled but not attended, between April 2016 and March 2020. We compared counts by local authority (LA) and financial quarter against the Office for Health Improvement and Disparities' Health Visitor Service Delivery Metrics (HVSDM) to identify a subnational subset of complete CSDS data. We explored the representativeness of this subset. Results During the study period, 10.2 million health visiting contacts were delivered to 2.4 million children in England. Of these, we identified 3.9 million mandated contacts based on CSDS codes and age at time of contact, which represented 44.7% of all mandated contacts reported in the HVSDM for the same period. There were 63 LAs with complete CSDS data in at least one quarter, which were broadly representative of English LAs overall. Variables related to staff characteristics were highly missing and only 13 LAs had four or more successive quarters of complete data needed for longitudinal, child-level analyses. Conclusions We identified a subnational subset of complete CSDS data, compared to external reference data, which can be used for health visiting research. Until improvements are made to its completeness, analyses (particularly those requiring longitudinal data) may not be generalisable to the whole child population.